Modern drama and the rhetoric of theater - Worthen, William B., 1955- (University of California Press, 1992)
The history of drama is typically viewed as a series of inert ""styles."" Tracing British and American stage drama from the 1880s onward, W.B. Worthen instead sees drama as the interplay of text, stage production, and audience. How are audiences manipulated? What makes drama meaningful? Worthen identifies three rhetorical strategies that distinguish an O'Neill play from a Yeats, or these two from a Brecht. Where realistic theater relies on the ""natural"" qualities of the stage scene, poetic theater uses the poet's word, the text, to control performance. Modern political theater, by contrast,